2019
DOI: 10.1073/pnas.1902280116
|View full text |Cite
|
Sign up to set email alerts
|

Translational implications of the anatomical nonequivalence of functionally equivalent cholinergic circuit motifs

Abstract: Biomedical research is at a critical juncture, with an aging population increasingly beset by chronic illness and prominent failures to translate research from "bench to bedside." These challenges emerge on a background of increasing "silo-ing" of experiments (and experimenters)-many investigators produce and consume research conducted in 1, perhaps 2, species-and increasing pressure to reduce or eliminate research on so-called "higher" mammals. Such decisions to restrict species diversity in biomedical resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…This commonality connects with mechanistic knowledge of how V1 activity is modulated. The primate-rodent difference in the magnitude and sign of V1 gain modulations we observed is in fact consistent with known differences in neuromodulatory inputs related to arousal in rodent and primate V1 [35,36]. In primates, the locations of ACh receptors allow cholinergic inputs to increase the activity of the majority of GABAergic neurons and hence suppress net activity via inhibition [37,38], but pharmacologically and anatomically distinct cholinergic influences in rodent likely exert more complex effects on net activity, including disinhibition which can increase net activity [15,17,39].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This commonality connects with mechanistic knowledge of how V1 activity is modulated. The primate-rodent difference in the magnitude and sign of V1 gain modulations we observed is in fact consistent with known differences in neuromodulatory inputs related to arousal in rodent and primate V1 [35,36]. In primates, the locations of ACh receptors allow cholinergic inputs to increase the activity of the majority of GABAergic neurons and hence suppress net activity via inhibition [37,38], but pharmacologically and anatomically distinct cholinergic influences in rodent likely exert more complex effects on net activity, including disinhibition which can increase net activity [15,17,39].…”
Section: Discussionsupporting
confidence: 88%
“…Second, although we found only small effects (relative to mouse) at the aggregate level, our results call for more specific investigations of modulations at the level of cell types and subcircuits [1, 11, 15, 16]. Such investigations may reveal more nuanced effects in primate V1, using tools that can better unpack the circuitry associated with factors such as cholinergic modulation, which are known to differ in important ways across rodent and monkey [35, 36]. Additionally, differences in feedback circuits also exist across the visual field representation within primate V1 [47].…”
Section: Discussionmentioning
confidence: 78%
“…The first issue is related to the anatomical difference of the cholinergic nuclei between rodents and primates, including the balance between cholinergic and non-cholinergic neurons in the basal forebrain. Also, the difference in the structural segregation and the cortical projections from NBM subdivisions between rodents and human has significant consequences for the cognitive and behavioral effects [77][78][79] . For example, in human, the anterior NBM projects its neurons more to the frontal lobe whereas the posterior part innervates the temporal region 80,81 .…”
Section: Discussionmentioning
confidence: 99%
“…Two search components were combined: electrical stimulation and the NBM, as described in Supplementary File. Considering that rodent studies often referred the NBM structure to its broader anatomical term, the basal forebrain due to the inherently indistinctive and less-differentiated nature of this structure in rodents than in primates, we therefore included the term "basal forebrain" in our search strategy 77,78 . However, articles which clearly specified the basal forebrain structure as non-NBM, such as the medial septum (Ch1) and the diagonal band of Broca (Ch2 and Ch3), were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Evolutionary divergence at molecular and cellular levels is multifaceted, including changes in the abundance of conserved cell types, changes in the genetic programs of conserved cell types, differential allocation of conserved cell types across locations, and evolution of new cell types ( 39 43 ). With these changes come alterations in localized circuit motifs: For example, the divergent structure but analogous function of cholinergic cortical circuits between macaques and rats ( 44 ) and the unique glutamatergic layer III microcircuits in the DLPFC involving (NMDAR) NR2B-dependent recurrent excitation in macaques, likely providing the basis for working memory and contributing to our understanding of the vulnerability of this region in schizophrenia ( 45 ). Moreover, a recent study ( 43 ) identified an abundant striatal interneuron type in primates that has no molecularly homologous cell population in rodents.…”
Section: The Need For Genetically Modified Nhps In Neuroscience Reseamentioning
confidence: 99%